2014
DOI: 10.1111/ajt.12561
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Is a Major Risk Factor for Mortality After Lung Transplantation

Abstract: Survival following lung transplant (LTx) remains significantly lower than after other solid organ transplants. Diabetes mellitus (DM) is a mortality risk factor not comprehensively studied in LTx recipients. Notably, neither the relation of time of DM onset to survival nor the actual causes of DM-associated excess mortality have been described. We determined DM status, DM diagnosis date and all-cause mortality in 386 consecutive adults who underwent LTx at our institution from January 1, 2001 to July 31, 2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 36 publications
2
64
2
2
Order By: Relevance
“…The increased mortality in patients with DM in our study is consistent with several retrospective studies (5,8,28) and with data from the ISHLT (2). However, a mechanism has not yet been demonstrated.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The increased mortality in patients with DM in our study is consistent with several retrospective studies (5,8,28) and with data from the ISHLT (2). However, a mechanism has not yet been demonstrated.…”
Section: Discussionsupporting
confidence: 93%
“…Chronic renal failure is another risk factor for post-Tx mortality, and pre-Tx DM increased chronic renal failure risk by 53% in LTRs (29). We have previously shown that bronchiolitis obliterans syndrome is the main cause of death after LTx, irrespective of DM status (8). DM may directly impair lung function in LTRs, as it does in the general population (30,31), and in patients with CF (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations